Professor Paweł Jokiel – a biography written in water - Tomaszewski, Edmund (Acta Geographica Lodziensia, 2024)
The article contains an overview of the scientific achievements of Professor Paweł Jokiel in his 45-year scientific career. The main research trends and the professor's contribution to the development of science against the background of selected publications have been discussed. His achievements in the teaching and organisational fields were also presented as well as interests and passions combining personal and professional life.